Fermentation And Purification Of Lipase By Burkholderia Metallica Using Column Reactor - Redza, Nur Ezzreen Zafhrina Mohamad (Universiti Sains Malaysia, 2020)
In this work, fermentation was conducted for the feedstock and purification of lipase by Burkholderia metallica using a column reactor. The targeted parameter for this research such as salt stability, types and concentrations of polyethylene glycol(PEG) and salt, pH of extraction solution and flowrate ml/s to see the performance of extractive purification system.